2018
DOI: 10.1002/jso.24963
|View full text |Cite
|
Sign up to set email alerts
|

Postmetastasis survival in high‐grade extremity osteosarcoma: A retrospective analysis of prognostic factors in 126 patients

Abstract: PMS in osteosarcoma patients was influenced by primary tumor-related factors such as histologic response to chemotherapy, as well as metastasis-related factors such as complete metastasectomy and metastasis site. A certain group of patients without such poor prognostic factors could be cured even after the development of metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 29 publications
3
24
1
Order By: Relevance
“…However, it is not easy to perform an en bloc tumor resection for spine osteosarcoma, and it exhibits strong local aggressiveness with a high rate of local recurrence. Moreover, osteosarcoma is likely to metastasize early through hematogenous spread (about 15–20%) [3,7,8]. Therefore, osteosarcoma has disastrous effects on individuals and society due to its major cohorts affected, undesirable prognosis, and early metastasis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is not easy to perform an en bloc tumor resection for spine osteosarcoma, and it exhibits strong local aggressiveness with a high rate of local recurrence. Moreover, osteosarcoma is likely to metastasize early through hematogenous spread (about 15–20%) [3,7,8]. Therefore, osteosarcoma has disastrous effects on individuals and society due to its major cohorts affected, undesirable prognosis, and early metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the prognosis of non-metastatic osteosarcoma, it may be extremely important to find the truly significant prognostic factors. In previous case series, factors such as age at diagnosis, tumor size and location, pathology, presence and location of metastases, surgical strategy, surgical margin, and histologic respond to chemotherapy have been reported to affect overall survival (OS) [4,813]. However, criteria used for evaluation of surgical treatment vary among centers and even different surgeons, which may increase the heterogeneity of samples.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the 5-year postmetastatic survival rate was 31% with a median length of 22 months. Local recurrence prior to metastasis, extrapulmonary metastasis, and poor histological response to preoperative chemotherapy were identified as negative prognostic factors [ 22 ]. In summary, the efficiency of follow-up surveillance programmes to detect local recurrences seems to be limited.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] However, osteosarcoma exhibits high local invasiveness and early distant metastasis, resulting in an unfavorable prognosis. [6][7][8] Osteosarcoma has a variety of histological subtypes, such as chondroblastic, fibroblastic, telangiectatic, and others. As a common subtype, chondroblastic osteosarcoma is characterized by a high proportion of the chondroid matrix.…”
Section: Introductionmentioning
confidence: 99%